Bacillus pumilus promotes the growth and nitrogen uptake of tomato plants under nitrogen fertilization - Masood, Sajid; Zhao, Xue Qiang; Shen, Ren Fang (Scientia horticulturae, 2020)
•Bacillus pumilus improves tomato growth and N uptake under N fertilization.•B. pumilus does not influence tomato growth or N uptake under no N fertilization.•B. pumilus-induced N2 fixation contributes to N uptake by tomato.•B. pumilus-induced N2 fixation is associated with bacterial nifH gene.•Leaf transpiration stream is involved in B. pumilus-enhanced N uptake. Some plant growth-promoting bacteria (PGPB) are capable of fixing atmospheric N2 and can be used to reduce nitrogen (N) fertilizer application in agriculture. Large amounts of N fertilizers are applied in tomato (Solanum lycopersicum L.). However, less attention has been given to the role of PGPB in the N nutrition of tomato. The present study was carried out under greenhouse conditions to investigate the principal mechanisms underlying PGPB-improved N nutrition in tomato. Tomato plants were grown in pots under –N (native soil N without N fertilization) or + N (supply 150 mg N kg–1 dry soil in the form of urea), with or without Bacillus pumilus (PGPB) inoculation. Nitrogen supply improved the growth of tomato, soil NH4+ concentration, and plant N uptake. Nitrogen increased the rhizobacterial population, bacterial nifH gene expression, and soil nitrogenase activity only with the inoculation of B. pumilus. B. pumilus inoculation improved the tomato growth, N uptake, soil NH4+ concentrations, rhizobacterial population levels, soil bacterial gene expression, and soil nitrogenase activity only under + N condition. These results suggest that the inoculation of B. pumilus improves the growth of tomato under the condition of additional fertilizer N supply due to an increase in N uptake by roots from B. pumilus-assisted fixed N in soil.